1999
DOI: 10.4269/ajtmh.1999.60.740
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the polymerase chain reaction in detection of Trypanosoma cruzi in Guatemalan Chagas' disease vectors.

Abstract: Abstract. For effective control programs, accurate assessment of Trypanosoma cruzi infection in vectors is essential and has traditionally been performed by microscopic examination. For particular vectors and not others, polymerase chain reaction (PCR) analysis of fecal samples recently has been shown to be an effective means of detection. The sensitivities of the PCR and microscopy for detection of T. cruzi in different anatomic sites were compared in the two major vectors of Guatemala, Triatoma dimidiata and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 11 publications
0
52
0
4
Order By: Relevance
“…Nevertheless, all negative filter paper samples revealed the 144 bp DNA fragment after addition of T. cruzi DNA thus confirming the inexistence of amplification inhibitor factors what was crucial to rule out the presence of inhibitors, that have already been reported by Breniere et al (1995) who used the same boiling procedure of the present study, and Araújo et al (2002) who used a more complex extraction procedure with phenol-chloroform extractions. Dorn et al (1999;2001) have associated amplification inhibition to the type of biological sample, suggesting that digestive tract samples, especially stomach contents are more prone to inhibit PCR. We decided to increase the number of insects in the second study group (lower parasitemia model) with a proportional reduction of the number of insects in the control group due to the loss of some insects during the first experiment (high parasitemia), and also because all negative triatomines did not generate any amplification during the first part of the study, taken into account that our capacity to breed and maintain triatomines was limited by the laboratory infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, all negative filter paper samples revealed the 144 bp DNA fragment after addition of T. cruzi DNA thus confirming the inexistence of amplification inhibitor factors what was crucial to rule out the presence of inhibitors, that have already been reported by Breniere et al (1995) who used the same boiling procedure of the present study, and Araújo et al (2002) who used a more complex extraction procedure with phenol-chloroform extractions. Dorn et al (1999;2001) have associated amplification inhibition to the type of biological sample, suggesting that digestive tract samples, especially stomach contents are more prone to inhibit PCR. We decided to increase the number of insects in the second study group (lower parasitemia model) with a proportional reduction of the number of insects in the control group due to the loss of some insects during the first experiment (high parasitemia), and also because all negative triatomines did not generate any amplification during the first part of the study, taken into account that our capacity to breed and maintain triatomines was limited by the laboratory infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Among different research groups, different PCR detecting systems have been reported for detecting T. cruzi and T. rangeli in the intestinal content from experimental and naturally infected vectors. In this sense, DORN et al (1999) 9 showed that the TC1/TC2 minicircle targed PCR assay was biased to T. cruzi since T. rangeli must constitute at least 75% of the sample in the presence of T. cruzi for detection by the PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Due to direct microscopic detection of trypanosomes, the traditional method for assessment of infection in vectors is not able to distinguish T. cruzi from T. rangeli infection, several polymerase chain reaction techniques have been developed 3,4,5,6,9,13,19,28,33,36,40,41 . However, current PCR assays used for mixed infection detection show some disadvantages such as the amplification of bands of similar size both in T. cruzi and T. rangeli 27,28 , the amplification of polymorphic fragments 11,19 , and bias to T. cruzi in the case of mixed T. cruzi and T. rangeli infection 9,33,36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular tools such as the Polymerase Chain Reaction (PCR) allow the analysis of multiple samples with high specificity and sensitivity. Previous reports have shown the applicability of PCR for epidemiological studies of T. cruzi (Brenière et al, 1995 ;Dorn et al, 1999 ;Shikanai et al, 1996). In this study, we compare the microscopic and PCR method, using T. cruzi (tc24) specific primers, for detecting T. cruzi infection in Triatoma dimidiata, one of the principal Ecuadorian vectors of Chagas' disease.…”
Section: Les Programmes De Contrôle De La Transmission Vectorielle Dementioning
confidence: 99%